(3WHbGJ GdTGaYjI GdcHQis - (3YHO GdhgGH Hf Ydj Hf YHO GdcGaj GdSHcj, CHh fUQ , JGL GdOjf , J (B771 (3g` s ((3YeQ Hf YHO Gddg Hf eMeO Hf eMehO GdefXQGhi s)
(3ChdgG (B:s
(3GdWHbI GdSGOSI CMeO Hf EHQGgje Hf GdMSf Hf LYaQ Hf CMeO Hf gTGe GdCehi GdPi cGf Cfg EPG CSeY bUjOg MaXgG s
(3BNQgG (B:s
(3eTeQ Pjdg dSjQ JTejQ Pi GdQLdg GdfTjW HGddg jG UHM dGJRQfG aGdUHM MQH dbhe dhW BNQ GdWHbGJ Ydi eG hLO HNW GdeUfa JZeOg Gddg HQMeJg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B184 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B225s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs